Green Finance: Analisis Implementasi Green Finance pada Perbankan Syariah Dalam Mewujudkan Suistainable Finance di Indonesia - Suharto Tentiyo (JIBF MADINA : Journal Islamic Banking and Finance Madina, 2023)
Analisis Implementasi Green Finance pada Perbankan Syariah Dalam Mewujudkan Suistainable Finance di Indonesia Tentiyo Suharto Sekolah Tinggi Agama Islam Negeri Mandailing Natal Email: tentiyosuharto18@gmail.com Abstract The concept of green finance, which basically encourages every economic activity to minimize its impact on the environment, has also been adopted by the banking world. One of them is through the concept of green banking or green bank. This greening movement in the realm of banking is known as green banking. Green banking is not only concerned with the world of financing, but also other programs that are environmentally sound. cause or result in environmental pollution or damage. This type of research is a qualitative research with a library research approach, research conducted by collecting information based on observations. Researchers also use library research as supporting literature to obtain data and information relevant to books or other sources related to Green Finance and Sustainable Finance. There are three main roles in this “green finance” system, namely: Greening the banking system, Greening, bond markets, Greening institutional investors. With the enactment of the sharia banking law and as a result of the implementation of prudent banking principles and the issue of bank soundness, the sharia banking sector will certainly be very good to environmental issues. Developing Islamic banking in its foundation is carried out on the basis of goodness in muamalah and support from various elements, both the role of the community, entrepreneurs and banks in developing the concept of sustainable green economic development for a better life. The components to achieve Sustainability are: Bank Customer Segment, Value Proposition, Network, Relationship to customers, Revenue or profit sharing, Human Resources, Activities, Partners, Cost Structure. Keywords: Implementation, Green Finance, Sustainable Finance, Banking Sharia, OJK, Sharia Economics, Financing, Environment, Green Banking